Belarus : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1998)
This paper reviews economic developments in the Republic of Belarus during 1996-98. Since 1996, the Belarusian authorities have sought to revive economic activity and raise living standards through the rapid expansion of credit and policies aimed at accelerating export growth, particularly to Russia. These policies led to the acceleration of officially measured economic growth, from close to 3 percent in 1996 to 10 1\2 percent in 1997 and 12 percent during the first quarter of 1998 (year over year).